TEORI MEDAN MAKNA DAN KONTEKSTUALITAS HUKUM ISLAM KONTEMPORER: REINTERPRETASI HADIS-HADIS ETIKA EKONOMI ISLAM DALAM WACANA SEMANTIK - Wahyu Hanafi, Nafi'ah, (Fakultas Syariah INSURI Ponorogo, 2019)
This study aims to describe the actualization of semantic field theory in the reinterpretation of the hadiths of Islamic economic ethics. This research uses descriptive interpretive method. Actualization of semantic field theory can be explained when want to know the meaning of a word then must know the meaning of the word associated with the previous word. If viewed from the nature of the semantic relationship, then the words are grouped into a semantic field divided into 1). sintagmatic 2). set field (paradigmatic). The results of this study explain 1). Hadiths about Islamic economic ethics narrated by Ahmad and Abu Dawud with the word focus